An Investigation into Gender Bias in Vietnamese Secondary School EFL Textbook Dialogues - Nguyễn, Thị Ngọc Hà (2020)
ABSTRACTThis investigation is a quantitative study of dialogues in eight EFL textbooks used in lower secondary schools in Vietnam. The chosen textbooks are Tiếng Anh 6 tập 1, Tiếng Anh 6 tập 2, Tiếng Anh 7 tập 1, Tiếng Anh 7 tập 2, Tiếng Anh 8 tập 1, Tiếng Anh 8 tập 2, Tiếng Anh 9 tập 1, andTiếng Anh tập 2. The aim is to investigate if there is any over-representation of female or male characters in the dialogues in the textbooks currently being used in Vietnam. This study was conducted over the dialogues of each textbook, and the researcher will look at four different typologies: (1) The number of times male/female character initiated dialogue; (2) The number of turns taken; (3) The number of characters; and (4) The number of words used. The findings show that gender over-representation occurs in all of the investigated textbooks. To be more specific, two of the eight textbooks over-represented female characters while the other six textbooks over-represented male ones. It is also worth mentioning that there is a shift from male-dominated dialogues to more female-dominate dialogues from 2013 to 2016. Some pedagogical implications have been suggested to textbooks writers and learners in terms of gender bias in textbook dialogues.